Atrophic Kidney Like Lesion: A Provisional Entity With Brief Review of Literature. (September 2022) - Narwal, Anubhav; Kaushal, Seema; Nakra, Tripti; Sharma, Mehar Chand; Kumar, Manoj
Atrophic kidney-like lesion (AKLL) is a provisional renal entity with distinct morphological and immunohistochemical features. It characteristically resembles thyroid-like follicular renal cell carcinoma (RCC) of kidney, an emerging renal entity. Very few patients of AKLL have been reported in the literature. We are hereby describing the clinicopathological features of AKLL in a 38-year-old man. The patient was incidentally found to have a renal mass and underwent radical nephrectomy. The morphological and immunohistochemical findings revealed features of AKLL. The patient on 24 months' post-operative period follow-up is alive without recurrence or metastasis.